2022
DOI: 10.3390/biom12030350
|View full text |Cite
|
Sign up to set email alerts
|

Roles of PI3K/AKT/mTOR Axis in Arteriovenous Fistula

Abstract: Renal failure is a worldwide disease with a continuously increasing prevalence and involving a rising need for long-term treatment, mainly by haemodialysis. Arteriovenous fistula (AVF) is the favourite type of vascular access for haemodialysis; however, the lasting success of this therapy depends on its maturation, which is directly influenced by many concomitant processes such as vein wall thickening or inflammation. Understanding the molecular mechanisms that drive AVF maturation and failure can highlight ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…High expression of EFNA4 is associated with tumor invasiveness and metastasis, making it an attractive therapeutic target. In previous studies, EFNA4 has been shown to function as an oncogene in a variety of malignancies and participate in the regulation of tumor cell growth and metastasis ( 8 - 12 ). In this study, through TCGA database analysis, we verified that EFNA4 is highly expressed in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High expression of EFNA4 is associated with tumor invasiveness and metastasis, making it an attractive therapeutic target. In previous studies, EFNA4 has been shown to function as an oncogene in a variety of malignancies and participate in the regulation of tumor cell growth and metastasis ( 8 - 12 ). In this study, through TCGA database analysis, we verified that EFNA4 is highly expressed in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Ephrin A4 ( EFNA4 ) is a ligand of the ephrin (EFN) family and is involved in the development of blood vessels and epithelium through the regulation of cell migration and repulsion ( 11 ). EFNA4 participates in the regulation of many signaling pathways, including the phosphoinositide 3-kinase (PI3K)/protein kinase B (PKB, also known as AKT) signaling pathway and EFN/EFN receptor (Eph) signaling pathway, among others ( 12 ). Previous study has shown that EFNA4 directly interacts with EFN receptor A2 (EPHA2) and promotes its phosphorylation at Ser897, recruits phosphoinositol-3-kinase regulatory subunit 2 (PIK3R2), and activates the glycogen synthase kinase-3β (GSK3β)/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular matrix components are expressed in various patterns during AVF maturation [ 48 , 49 ]. The PI3K-AKT signaling pathway is involved in multiple functions, including extracellular matrix formation, wall thickening remodeling, immune system activation, and inflammation reduction [ 50 ]. Furthermore, it often performs contrasting functions in the AVF process.…”
Section: Discussionmentioning
confidence: 99%
“…The last one, class III PI3K, has only a catalytic subunit, VPS34 [96]. Regarding distribution, PI3Kα, PI3Kβ, PI3KC2α, and PI3KC2β isoforms are relatively ubiquitously expressed, PI3Kγ and PI3Kδ are found especially in leukocytes, while PI3KC2γ is found in the liver [98].…”
Section: Overview Of the Pi3k/akt/mtor Signaling Pathwaymentioning
confidence: 99%